Relationship between plasma leucine-rich α-2-glycoprotein 1 and urinary albumin excretion in patients with type 2 diabetes - Chung, Jin Ook; Park, Seon-Young; Cho, Dong Hyeok; Chung, Dong Jin; Chung, Min Young (Frontiers in Endocrinology, 2023)
To explore the relationship between plasma leucine-rich α-2-glycoprotein 1 (LRG1) level and the degree of urinary albumin excretion in patients with type 2 diabetes.We evaluated 332 patients with type 2 diabetes in a cross-sectional study.Result The plasma LRG1 level differed significantly according to the quartiles of urinary albumin excretion (Q1 [<7.7 mg/g], 17.1 μg/mL; Q2 [7.7-15.0 mg/g], 17.5 μg/mL; Q3 [15.1-61.4 mg/g], 18.6 μg/mL; Q4 [≥61.5 mg/g], 22.3 μg/mL; p for trend = 0.003) under adjustment with other covariates. A positive correlation was found between plasma LRG1 level and urinary albumin excretion (ρ = 0.256, p <0.001). According to a multivariate model, the association between LRG1 and urinary albumin excretion remained significant, under adjustment for confounding factors (β = 0.285, p <0.001).Plasma LRG1 level was independently associated with urinary albumin excretion in patients with type 2 diabetes. This study suggests that LRG1 may be associated with increased excretion of urinary albumin in the early stages of diabetic nephropathy.